On optimal non-linear taxation and public good provision in overlapping generations economy - Pirttilä, Jukka, 1970-; Tuomala, Matti (Helsinki : Government Institute for Economic Research, 1999)
Tiivistelmä.
Keywords: pääomaverotus; tarjonta; tulovero; verotus; kapitalbeskattning; utbud; inkomstskatt; beskattning; capital income taxation; kestokulutusjulkishyödykkeet; non-linear income taxation; public good provision